Viewpoint: Food insecurity among college students: A case for consistent and comparable measurement. (May 2021) - Ellison, Brenna; Bruening, Meg; Hruschka, Daniel J.; Nikolaus, Cassandra J.; van Woerden, Irene; Rabbitt, Matthew P.; Nickols-Richardson, Sharon M.
Highlights: There is increased interest in food insecurity rates on college campuses. College food insecurity rates vary widely in the published literature. No food insecurity measure has been validated for use with college students. Consistent and comparable measurement is critical for efficient policy design. Abstract: A growing body of research among college students has estimated remarkably high levels of food insecurity when compared to food insecurity estimates from the general population over the past decade, with recent literature reviews reporting average prevalence rates of 33–51% compared to 9.8% among U.S. adults. Given these high rates of food insecurity, policymakers at the state- and federal-levels are considering legislation to better understand and ultimately alleviate food insecurity in the college student population. Further, the National Postsecondary Student Aid Study will soon collect national surveillance data on college student food insecurity. However, emerging research suggests that existing food insecurity measurement tools may not perform as expected when used with college students. Indeed, there is no food insecurity measure that has been validated for use with college students. The purpose of this commentary is to discuss the current state of food insecurity measurement among college students and set a course for more meaningful measurement in the college-student population that produces consistent and comparable estimates of food insecurity.